Experimental characterization of compression performance of carbonâbasalt hybrid filament wound pipes before and after impact - Farhood, N.H. (Begell House Inc., 2020)
This paper describes the effects of different stacking sequences and fiber content ratios on the compression and the compression-after-impact (CAI) behavior of hybrid carbonâbasalt (CâB) fiber-reinforced polymer pipes. Hybrid composite pipes composed of eight layers of Â± 55Â°/90Â°2/Â± 55Â°/90Â°2 were manufactured utilizing the filament winding technique. A series of axial compression tests were carried out on the composite pipes based on ASTM D3410 standard for the nonimpacted and impacted specimens at 100-J impact energy. Residual compressive strength, damage tolerance and failure modes were examined and analyzed for different composite pipe configurations before and after an impact. The results showed that the specimens with fiber content ratio 50:50 CâB fibers exhibited better impact resistance as compared with specimens of fiber content ratio 75:25 CâB fibers, under the same conditions of impact energy. Furthermore, despite carbon fiber sustaining highest compressive force among nonimpacted samples, it exhibited the highest percentage reduction in residual compressive force after impact, at 62%, as such having the worst impact damage tolerance for a given energy level. Specimens with basalt fiber on the outer surface (i.e., Nos. 3 and 6) and alternative fiber specimens (i.e., Nos. 5 and 8), which showed a good response to the impact, sustain high values of the compressive loads for both content ratios. Â© 2020 by Begell House, Inc.